Answers

  • Brainly User
2015-03-21T18:27:07+05:30
(22+(-20)+(29-(-3)-32+95-2x+6x (22-20)+(29+3)-32+95+4x (2)+(32)-32+95+4x 34-32+95+4x 129-32+4x 97+4x if this is equal to zero than 97+4x=0 4x=-97 x=-97/4
0
2015-03-21T18:28:52+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
22-20+29+3-32+95-2x+6x=0
2+29+3-32+95-2x+6x=0
34-32+95-2x+6x=0
2+95-2x+6x=0
97+4x=0
4x = -97
x = -97/4
x=-24.25
1 5 1
no thnx also ok?
:)'
:))))))))))))))))))))))))))))))
aha come to cht box pilla
ok pilla